1984
DOI: 10.1159/000145910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guanethidine-Induced Sympathectomy on Osteoblastic Activity in the Rat Femur Evaluated by <sup>3</sup>H·Proline Autoradiography

Abstract: Osteoblastic activity in the rat femur was assessed following sympathectomy by injections of guanethidine sulfate from birth to 14 days of age. At ages 30, 45 and 90 days, osteogenesis was monitored by quantitative autoradiography using 3H-proline. Grain counts over periosteal osteoblasts of the femoral diaphysis showed a significant reduction in the uptake of 3H -proline in sympathectomized rats. The results indicate that the sympathetic innervation of bone influences osteoblastic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
0
19
1
Order By: Relevance
“…In-vitro studies in different lines of bone cells, as well as in-vivo studies in experimental animals, have demonstrated effects of b-adrenergic receptor agonists and antagonists on bone metabolism, but the results reported have been conflicting. In different studies, b-adrenergic stimulation and inhibition have been reported to cause Antihypertensive drugs and fracture risk Rejnmark et al 585 anabolic as well as catabolic effects on bone [23][24][25][26][27]. In humans, there are only few and conflicting data on the effects of beta-blockers on bone metabolism and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro studies in different lines of bone cells, as well as in-vivo studies in experimental animals, have demonstrated effects of b-adrenergic receptor agonists and antagonists on bone metabolism, but the results reported have been conflicting. In different studies, b-adrenergic stimulation and inhibition have been reported to cause Antihypertensive drugs and fracture risk Rejnmark et al 585 anabolic as well as catabolic effects on bone [23][24][25][26][27]. In humans, there are only few and conflicting data on the effects of beta-blockers on bone metabolism and fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…The sympathetic nervous system influences both osteoblast and osteoclast activity. Chemically sympathectomized mice demonstrate a decrease in osteoblastic activity, with reduced uptake of collagen precursors and deposition of the bone matrix [145,146]. Both β-adrenergic and glutamatergic signaling influences osteoblast function and bone remodeling.…”
Section: The Role Of Neurons In Mesodermal Tissuesmentioning
confidence: 99%
“…Singh et al (1981) and Herskovits and Singh (1984) demonstrated the modulation of osteoblastic activity following sympathectomy induced by guanethidine, which specifically destroys sympathetic adrenergic fibers.…”
Section: Effect Of Sympathectomymentioning
confidence: 99%